2000
DOI: 10.1038/35021052
|View full text |Cite
|
Sign up to set email alerts
|

Fear memories require protein synthesis in the amygdala for reconsolidation after retrieval

Abstract: 'New' memories are initially labile and sensitive to disruption before being consolidated into stable long-term memories. Much evidence indicates that this consolidation involves the synthesis of new proteins in neurons. The lateral and basal nuclei of the amygdala (LBA) are believed to be a site of memory storage in fear learning. Infusion of the protein synthesis inhibitor anisomycin into the LBA shortly after training prevents consolidation of fear memories. Here we show that consolidated fear memories, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

122
2,297
19
27

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,391 publications
(2,465 citation statements)
references
References 25 publications
122
2,297
19
27
Order By: Relevance
“…The latter method is also in line with human and animal conditioning studies, where a single unreinforced CS is usually used for memory reactivation (e.g. Nader, Schafe, & LeDoux, 2000; Schiller et al, 2010). The intervention is then placed during expectation of upcoming trauma, which fits with the view that ‘warning signals’ are a key component of a trauma memory.…”
Section: Discussionmentioning
confidence: 81%
“…The latter method is also in line with human and animal conditioning studies, where a single unreinforced CS is usually used for memory reactivation (e.g. Nader, Schafe, & LeDoux, 2000; Schiller et al, 2010). The intervention is then placed during expectation of upcoming trauma, which fits with the view that ‘warning signals’ are a key component of a trauma memory.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, the memory reconsolidation literature suggests that even established memories become labile again upon reactivation from LTM and need to re‐stabilize and reconsolidate to persist (Nader, 2003; Nader, Schafe, & Le Doux, 2000; Walker et al, 2003). Therefore, the effects of Tetris on intrusive memories could be observed after any length of post‐encoding delay in principle, as long as the memory is labile and thus amenable to interference, for example, as has been tested 24 h or more after encoding (James et al, 2015).…”
mentioning
confidence: 99%
“…Loftus & Palmer, 1974), but, prior to their groundbreaking work on reconsolidation (e.g. Nader, Schafe, & LeDoux, 2000), behavioural neuroscientists believed that emotional memories were indelible (LeDoux, Romanski, & Xagoraris, 1989). A seminal study by Nader et al (2000) brought these two research disciplines closer by demonstrating that consolidated memories can indeed be changed.…”
mentioning
confidence: 99%
“…Nader, Schafe, & LeDoux, 2000), behavioural neuroscientists believed that emotional memories were indelible (LeDoux, Romanski, & Xagoraris, 1989). A seminal study by Nader et al (2000) brought these two research disciplines closer by demonstrating that consolidated memories can indeed be changed. Nader et al showed that memories are impaired when the reconsolidation process is disrupted, by injecting rodents with a pharmacological agent (i.e.…”
mentioning
confidence: 99%